2014
DOI: 10.1007/s13204-014-0381-7
|View full text |Cite
|
Sign up to set email alerts
|

New generation of bactericidal silver nanoparticles against different antibiotic resistant Escherichia coli strains

Abstract: Biosynthesis of silver nanoparticles (AgNPs) with ecofriendly plant extracts contains different phytochemicals act as both reducing and capping agents forming stable and shape-controlled AgNPs. The present study deals with the synthesis of AgNPs using the aqueous leaf extract of Coleus aromaticus and to evaluate the bactericidal activity against three antibiotic resistant Escherichia coli strains. The AgNPs are characterized using UV-Visible Spectroscopy, Scanning Electron Microscope coupled with X-ray Energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 46 publications
2
22
0
Order By: Relevance
“…5). The similar result has been observed with silver NPs synthesized with plant extracts [7,9] and fungal extract [29].…”
Section: Scanning Electron Microscopy (Sem) Analysissupporting
confidence: 86%
See 1 more Smart Citation
“…5). The similar result has been observed with silver NPs synthesized with plant extracts [7,9] and fungal extract [29].…”
Section: Scanning Electron Microscopy (Sem) Analysissupporting
confidence: 86%
“…TEM images showed that the particle size ranged from 19-52 nm. The particles are spherical, rectangular, a few with striations, uniformly distributed without any aggregation [9].…”
Section: O R P H O L O G Y O F G R E E N S I L V E R N P S W I T H mentioning
confidence: 99%
“…Due to the presence of negative charge on the surface, agglomeration of Tb-AgNPs in aqueous solution was prevented, and long-term stability was also allowed. This clearly indicated that the nanoparticles were stable because the minimum charge required to stabilize the nanoparticles was +30 mV or −30 mV [40,[13][14]. The results revealed and concluded that the biosynthesized Tb-AgNPs with the fruit extract of Terminalia belarica were very stable in aqueous environment.…”
Section: Analysis Of Zeta Potential Of Green Tb-agnpsmentioning
confidence: 86%
“…So, green chemistry methods were found to be a good alternative for biosynthesis of metallic AgNPs; they were nonhazardous, simple, inexpensive and environment friendly. Green silver nanoparticles gained their potential in antibacterial, antifungal, anticancer and biomedical applications [9][10][11][12][13][14][15]. The plant extracts have more potential in the synthesis of metal nanoparticles as they contain polyphenols, alkaloids, fatty acids, proteins, flavonoids which help reducing and capping agents.…”
Section: Introductionmentioning
confidence: 99%
“…AgNPs cause toxicity to the bacterial cell constituents, damage to mitochondria in particular, and result in depletion of ATP which enhances the production of ROS. Then there was a double impact of both ROS and AgNPs on the nucleus of Epi-fluorescent microscopic images of mixed bacterial species isolated from drinking water PVC pipeline a initial-2 h, b 2-4 h, c 4-6 h, d 6-7 h and after during interfacial contact studies in the presence of nanoparticles loaded in nutrient agar medium bacterial cell leads to oxidation of DNA causing the death of the bacterial cell (Venkata Subbaiah et al 2014). Similar results were observed by previous investigators for ZnO nanoparticles (Raghupathi et al 2011;Sivakumar et al 2010).…”
Section: Antibacterial Activitymentioning
confidence: 99%